Baeckea frutescens L. Promotes wound healing by upregulating expression of TGF-β, IL-1 β, VEGF and MMP-2 - Safwan Kamarazaman, Ihsan; Sui Kiong, Ling; Nik Hasan, Mohd Kamal; Basherudin, Norlia; Mohd Kasim, Nur Aini; Ali, Aida Azlina; Ramli, Salfarina; Maniam, Sandra; Johari James, Richard; Rojsitthisak, Pornchai; Halim, Hasseri (Elsevier, 2024)
Baeckea frutescens L. has been traditionally used for treating snakebites and is known to possess antifebrile and hemostatic properties. These properties are closely related to wound healing. This study aimed to evaluate the wound healing properties of B. frutescens leaves extract (BFLE) in vitro and in vivo. The in vitro study focused on proliferation, migration, and expression of TGF-β, IL-1β, VEGF, and MMP-2 genes and proteins. The in vivo study included excisional wound healing, histology, and tensile strength studies. The ethanolic extract of B. frutescens (BFLE) was tested for its effects on proliferation and migration using keratinocytes (HaCaT) and fibroblasts (BJ) cells. Gene and protein expression related to wound healing were analyzed using real-time PCR and Western blot assays. The wound healing properties of BFLE were evaluated in vivo using Wistar albino rats, focusing on excisional wound healing, histology, and tensile strength studies. The BFLE displayed significant proliferative and migratory effects on keratinocytes and fibroblasts cells, while upregulating the expression of TGF-β, IL-1β, VEGF, and MMP-2 genes and proteins. BFLE also exhibited significant wound healing effects on Wistar albino rats’ excisional wounds and improved the overall tensile strength. The results suggest that BFLE has strong wound healing properties, as demonstrated by its ability to increase keratinocytes and fibroblasts proliferation and migration, upregulate genes and proteins involved in the wound healing process, and improve wound healing rates and tensile strength. The findings of this study provide important insights into the potential use of B. frutescens as a natural wound healing agent.